Voicing passion: The emotional economy of songwriting. (April 2015) - Long, Paul; Barber, Simon
This article examines articulations of the role of passion in accounts of the life and work of the songwriter. It draws upon a range of interviews with successful artists captured in the Sodajerker On Songwriting podcast. It is suggested that these interviews capture the 'voicing' of the conventions of creativity in popular music, exploring a context in which passionate motivation, expression and understanding of the (potentially) affective responses to songs are paramount to the labour of the songwriter. The article explores how the core of this labour deals in emotion, attempting to articulate feelings in recognisable, tradable form. This is a process that is both instrumentally rationalised but often felt to be a deeply authentic process, understood (and believed) to spring from the individual's emotional experience, so conferring identity in a generic field. In light of current debates about the nature of creative work and emotional labour, the accounts drawn upon here can be seen to epitomise many of the qualities of what constitutes 'good work' through a mode of self-actualisation.